Compiling a Guide to Open Access Historical News Sources from Slavic, East European, and Eurasian Countries. (2nd October 2021) - Zitser, Ernest A.; Horbal, Bogdan
ABSTRACT: The digitization of historical news sources – both print and audio-visual – has altered the information landscape for researchers in all scholarly disciplines that investigate the past. Thanks to the initiative of nonprofit cultural heritage institutions, commercial enterprises, and joint public-private partnerships, researchers now have a plethora of electronic resources at their disposal. Unfortunately, only a portion of this data is freely available online, and what is available is generally scattered all over the internet. While guides to contemporary (currently active) news media outlets and newspapers abound, historical news sources are more difficult to locate. This article describes the authors' efforts to compile and publish an online guide to open access historical news sources from Slavic, East European, and Eurasian countries. It outlines the selection criteria, describes the guide's layout, and provides a survey of preliminary usage statistics.